KONTRIBUSI GOOD CORPORATE GOVERNANCE UNTUK MENGURANGI TERJADINYA AUDIT DELAY - Gustita Arnawati Putri; Yoppi Syahrial (Jurnal Penelitian Ekonomi dan Bisnis, 2019)
The delay of audit report being able to mislead stakeholders, especially investors in taking decision is the main issue of the research. The research objective is to prove empirically contribution of good corporate governance mechanism to decrease the audit delay. Banking companies listed in Indonesia stock exchange within 2011-2013 are the samples of the research. Multiple regression analysis, preceded by classical assumption test is used as analysis tool in the research. The research findings partially showed that managerial and institutional ownership did not affect to audit delay, while proportion of independent commissionairy boards significantly affected to audit delay. Nevertheless, simultaneously managerial and institutional ownership as well as proportion of independent commissionary boards and the number of audit committee significantly affected to audit delay.